Ash formation mechanisms during combustion/co-firing of biomass and coal - Shah, Kalpit Vrajeshkumar (Curtin University, 2010)
In case of PF firing, solid fuels such as coal and biomass undergo various chemical and physical transformations (devolatilization, char oxidation, fragmentation and gas to particle conversion followed by nucleation, coagulation and condensation etc.) just in milliseconds after fuel enters to the furnace. These transformations depend on several operating parameters (temperature, pressure, heating rate etc.) along with several chemical and physical properties (ash, moisture content, density, porosity, mineral matter composition and their association in the fuel matrix, particle size, shape and density etc.). The resultant ash formed during combustion after such parallel transformations in relation with several physical and chemical transformations along with the operating parameters will have different particle sizes and mineralogical composition compare to the original fuel.The scope of this research work is to perform the experimental and modelling work to investigate the ash formation process in terms of particle sizes and their mineralogical composition after combustion. A vast experimental study was planned in the lab scale combustion simulator at ECN with six biomass and two coals (Bark, wood chips, waste wood, saw dust, olive residue, straw, UK and a Polish etc.) under typical PF-firing conditions. Ash release, conversion, size reduction and size distribution alongside with the change in inorganic chemical compositions, are derived at different char burn out levels in the reactor at 20, 90, 210 and 1300 milliseconds of residence times. Several of the past observations made in the literature review are reconfirmed with performed set of experiments. A qualitative predictive tool is also suggested to envisage the extent of first line physical transformations. Based on the extensive data pool at hand, a simple but reliable (R2 >0.95) set of linear correlations have been proposed to predict the elemental release of potassium, sodium, chlorine and sulfur.It is also concluded that such linear expressions can be particularly effective for the prediction of elemental release from the fuels of similar characteristics, such as woody biomass. Mathematical model is developed to predict the particle size after combustion by simplifying Dunn-rankin’s particle population balance model analytically and kinetically. Ash formation modelling has also been attempted. The developed understanding and models can be further used for the investigations of several ash related problems during combustion and co-firing such as slagging, fouling, corrosion and erosion etc.